Two new species of Perinereis Kinberg, 1865 (Annelida: Nereididae) from the rocky shore of Maharashtra, India, including notes and an identification key to Group 1 - Prajapat, Vaishali; Villalobos-Guerrero, Tulio F.; Vachhrajani, Kauresh D. (European Journal of Taxonomy, 2024)
Two new species of Perinereis with single bar-shaped paragnaths on area VI (Group 1) from the rocky shores of Mumbai, Maharashtra, India, are described with barely (Subgroup 1A) or largely (Subgroup 1B) expanded proximal region of dorsal ligule in posterior parapodia. Perinereis malabarensis sp. nov. can be distinguished from the morphologically similar 1B species P. euiini Park & Kim, 2017 by the paragnath count in area I, the laterally isolated paragnaths in area III, and the length of the dorsal cirrus and dorsal ligule. Additionally, P. misrai sp. nov. is more similar to 1A species P. falsovariegata Monro, 1933 and P. villalobosi Rioja, 1947, but differs by the paragnath count in areas III–V and VII–VIII, the isolated paragnaths in area III, and the number of rows in the anterior band of areas VII–VIII. The morphological characters of the current 44 species within Perinereis G1 are compared, and an identification key to the species belonging to this group is also provided.